Tingkat Kecemasan Pasien Dan Keluarga Yang Rawat Inap Di RSPW Malang Selama Pandemi Covid-19 - Ardiyani, Vita Maryah; Sutriningsih, Ani (Universitas Tribhuwana Tunggadewi, 2022)
Increased anxiety is a common mental health problem during Covid-19. Anxiety can cause symptoms of insomnia, poor concentration, irritability, reduced productivity, interpersonal conflict, stigma, and fear of transmission to vulnerable groups. The purpose of this study was to identify the anxiety level of patients and families who were treated at Panti Waluya Sawahan Malang Hospital during the pandemic.Covid-19. This type of research is descriptive with a cross-sectional approach. The study population was all patients and their families who were treated at RSPW Malang during Covid-19, with a total sampling technique of 20 people. The research variable is the level of anxiety. The instrument used was a questionnaire containing the general identity of the respondent, including the respondent's name, age, gender, and education. The anxiety level instrument uses the HRS-A (Hamilton Rating Scale for Anxiety) which consists of 14 question items. Data were analyzed descriptively and presented in a frequency table. The results of the study found that 70% of respondents had a moderate level of anxiety. Further research is suggested to study other factors related to anxiety in patients and families in the hospital.